2020
DOI: 10.1200/jco.19.02263
|View full text |Cite|
|
Sign up to set email alerts
|

Growth Rates of Genetically Defined Renal Tumors: Implications for Active Surveillance and Intervention

Abstract: PURPOSE Published series of growth rates of renal tumors on active surveillance largely consist of tumors without pathologic or genetic data. Growth kinetics of genetically defined renal tumors are not well known. Here, we evaluate the growth of genetically defined renal tumors and their association with patient clinical and genetic characteristics. PATIENTS AND METHODS We evaluated patients with an inherited kidney cancer susceptibility syndrome as a result of a pathologic germline alteration of VHL, MET, FLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Even young family members should consider genetic testing as uveal and ocular melanomas may present as early as in the teenage years ( 6 , 21 ). Screening renal ultrasound, MRI, or urinalysis for renal cell carcinoma could also be considered ( 21 ), as these patients are prone to renal cell carcinoma and BAP1 mutated renal tumors appear to grow at a faster rate than kidney cancers driven by other mutations such as in von Hippel-Lindau disease ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even young family members should consider genetic testing as uveal and ocular melanomas may present as early as in the teenage years ( 6 , 21 ). Screening renal ultrasound, MRI, or urinalysis for renal cell carcinoma could also be considered ( 21 ), as these patients are prone to renal cell carcinoma and BAP1 mutated renal tumors appear to grow at a faster rate than kidney cancers driven by other mutations such as in von Hippel-Lindau disease ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 292 genetically defined patients, growth rates were analyzed from 435 tumors. Bap1-deficient tumors had the fastest growth rate (median 0.6 cm/year), while tumors with MET-activated tumors had the slowest growth rate (0.015 cm/year) [ 56 ].…”
Section: Clinical Managementmentioning
confidence: 99%
“…The evaluation of the growth rates of a cohort of 292 patients with genetically defined renal tumors and showed that BAP1-deficient tumors are those growing at the fastest rates [ 38 ].…”
Section: Hereditary Bap1 Tumor Syndromementioning
confidence: 99%